Kealpaan Pembuatan Akta Pemberian Hak Tanggungan Berdasarkan Surat Kuasa Membebankan Hak Tanggungan - Erna Erna; Edith Ratna M.S. (Notarius, 2022)
AbstractThe granting of dependent rights is a deed made by the land deed official called PPAT concerning the object of dependent rights that are within the working area of PPAT. Deed of granting dependent rights (PPAT) is a deed governing the granting of dependent rights between crediors and debtors concerning debtor’s debt to creditors, the object of guarantee in the form of land, in addition to also can be objects that include or contained on the land. Provision of dependent rights to guarantee the repayment of debtor’s debt to the creditor concerned, in order to be guaranteed repayment. APHT must be done by the dependent rights giver, but for a special situation can be made a deed of power of attorney imposing dependent rights called SKMHT SKMHT deed in addition to ppat is also made by notary public. Failure in the creation of the deed of granting of dependent rihts causes it cannot be registered the right of dependents on land, therefore it is very important the principle of prudence by the land deed official in the making of the deed.keywords: responsibilities; land deed officials; granting of dependent rightsAbstrakPemberian hak tanggungan adalah akta yang dibuat oleh Pejabat Pembuat Akta Tanah yang disebut PPAT mengenai objek hak tanggungan yang berada dalam wilayah kerja PPAT. APHT yaitu akta yang mengatur tentang pemberian hak tanggungan antara kreditor dan debitor mengenai hutang debitur kepada kreditor, objek jaminannya berupa tanah, selain itu juga dapat benda-benda yang meliputi atau yang terdapat diatas tanah tersebut. Pemberian Hak Tanggungan untuk menjaminan pelunasan hutang debitor terhadap kreditor yang bersangkutan, agar terjamin pelunasannya. APHT harus dilakukan oleh pemberi hak tanggungan, tetapi untuk suatu keadaan khusus dapat dibuat akta SKMHT. Akta SKMHT selain dibuat PPAT juga dibuat oleh Notaris. Kealpaan dalam pembuatan APHT menyebabkan tidak dapat didaftarkan Hak Tanggungan Atas Tanah, oleh karena itu sangat penting prinsip kehati-hatian oleh Pejabat Pembuat Akta Tanah dalam pembuatan akta.kata kunci: tanggung jawab; pejabat pembuat akta tanah; pemberian hak tanggungan